1994
DOI: 10.1016/0735-1097(94)90187-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of left ventricular pressure on sonicated albumin microbubbles: Evaluation using an isolated rabbit heart model

Abstract: The major cause of systolic decrease in contrast enhancement is periodic bubble compression (as opposed to bubble destruction) induced by high systolic pressures. The minor progressive decrease in end-diastolic videointensity reflects the degree of instability of Albunex microbubbles under left ventricular pressures. However, the clinical impact of these destructive effects is likely to be only minor because of the rapid transit of microbubbles through the left heart chambers and myocardial microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 7 publications
1
11
1
Order By: Relevance
“…Thus our results agree with those of several studies, 8,9,13 but disagree with those of Mor-Avi et al 2 The reason͑s͒ for this discrepancy is ͑are͒ not clear. In the MorAvi et al study, 2 the microbubbles were contained in a latex balloon within the left ventricle, and were thus subjected to no fluid flow other than that resulting from the application of the interrogating US.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Thus our results agree with those of several studies, 8,9,13 but disagree with those of Mor-Avi et al 2 The reason͑s͒ for this discrepancy is ͑are͒ not clear. In the MorAvi et al study, 2 the microbubbles were contained in a latex balloon within the left ventricle, and were thus subjected to no fluid flow other than that resulting from the application of the interrogating US.…”
Section: Discussioncontrasting
confidence: 68%
“…Right heart contrast is readily attained by intravenous injection of the agent, but left heart contrast decreases sharply during systole. 1,2 This effect appears to result from systolic pressure.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Shapiro et al [50] observed similar effects. In Moravi et al [46], an 8 per cent decrease in video intensity over 25 heart cycles owing to bubble destruction was observed. In Vuille et al [51], Albunex bubbles were suspended in saline solution and imaged at 2.5 MHz; the rate at which contrast disappeared was greater at higher pressures by multiples of two, three and nine, respectively, for the 0.06, 0.13 and 0.19 atm (6, 13 and 19 kPa) measurements.…”
Section: Blood Pressurementioning
confidence: 99%
“…An early study on this by Fairbank & Scully [45] reported that changes in the ambient pressure of the order of 0.2 atm (20 kPa) gave an observable shift in the resonant behaviour of gas bubbles of radii between 30 and 40 mm. Using a rabbit heart model, Moravi et al [46] observed an approximately 20 per cent decrease in video intensity for albumin-coated bubbles during systole compared with diastole owing to the pressure difference. Shi [29] has compared scattered signals from Levovist, a galactose-based bubble, at different harmonic frequencies as a function of ambient pressure.…”
Section: Blood Pressurementioning
confidence: 99%